2010
DOI: 10.1093/jxb/erq288
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-regulated β-amylase (BAM1) triggers diurnal starch degradation in guard cells, and in mesophyll cells under osmotic stress

Abstract: BAM1 is a plastid-targeted β-amylase of Arabidopsis thaliana specifically activated by reducing conditions. Among eight different chloroplast thioredoxin isoforms, thioredoxin f1 was the most efficient redox mediator, followed by thioredoxins m1, m2, y1, y2, and m4. Plastid-localized NADPH-thioredoxin reductase (NTRC) was also able partially to restore the activity of oxidized BAM1. Promoter activity of BAM1 was studied by reporter gene expression (GUS and YFP) in Arabidopsis transgenic plants. In young (non-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
170
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(184 citation statements)
references
References 43 publications
(79 reference statements)
13
170
0
1
Order By: Relevance
“…Mutant studies substantiate the hypothesis that BAM1 induction is critically important in the osmotic stress response. As first reported by Valerio et al (2011), we also found that bam1 mutants had reduced starch degradation in response to was used for confirmation. BAM1 was detected using polyclonal antibody raised against recombinant BAM1.…”
Section: Differential Regulation and Isoform Subfunctionalization Defsupporting
confidence: 79%
See 3 more Smart Citations
“…Mutant studies substantiate the hypothesis that BAM1 induction is critically important in the osmotic stress response. As first reported by Valerio et al (2011), we also found that bam1 mutants had reduced starch degradation in response to was used for confirmation. BAM1 was detected using polyclonal antibody raised against recombinant BAM1.…”
Section: Differential Regulation and Isoform Subfunctionalization Defsupporting
confidence: 79%
“…Under standard growth conditions, BAM1 is preferentially and highly expressed in guard cells, whereas BAM3 is considerably less abundant (Horrer et al, 2016). Consistent with the gene expression pattern, bam1 mutants have elevated guard cell starch levels compared with the wild type, whereas bam3 accumulates starch in this cell type similarly to the wild type (Horrer et al, 2016;Valerio et al, 2011). Altogether, these findings indicate that BAM1 and BAM3 are active under different conditions and in a cell typespecific manner.…”
Section: Differential Regulation and Isoform Subfunctionalization Defsupporting
confidence: 65%
See 2 more Smart Citations
“…The amplicon was digested with EcoRI and ligated into a modified pGreen0029 binary vector upstream of the GUS coding sequence fused with the nopaline synthase terminator (Valerio et al, 2011). The obtained vector was named pGAPC1-GUS.…”
Section: Dna Constructsmentioning
confidence: 99%